2022
DOI: 10.21273/horttech04895-21
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Colored Shading Nets on the Growth and Water Use Efficiency of Sweet Pepper Grown under Semi-arid Conditions

Abstract: Colored shading nets have been increasingly studied in semi-arid crop production systems, primarily because of their ability to reduce solar radiation with the attendant reductions in air, plant, and soil temperatures. However, there is a paucity of research concerning the impact of colored shading nets on various crops grown under semi-arid environments, particularly the sweet pepper (Capsicum annum) production system. This study aimed to investigate the effects of three colored shading net treatments (i.e., … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Mirrored roofing tiles would reduce heat wave mortality and energy system overload exacerbated by the urban heat island effect (Millstein and Fischer, 2014;Trlica et al, 2017). Replacing colored nets in agriculture with mirrors could improve productivity by reducing heat stress and agricultural water usage (Munywoki, 2017;Mohawesh et al, 2021). Preliminary experimental data suggest agricultural soil cooling by up to 4°C at a depth of 10 cm at mid-latitude (43°N), with cooler soil storing more carbon (Hartley et al, 2021).…”
Section: Potential Methods For Direct Climate Coolingmentioning
confidence: 99%
“…Mirrored roofing tiles would reduce heat wave mortality and energy system overload exacerbated by the urban heat island effect (Millstein and Fischer, 2014;Trlica et al, 2017). Replacing colored nets in agriculture with mirrors could improve productivity by reducing heat stress and agricultural water usage (Munywoki, 2017;Mohawesh et al, 2021). Preliminary experimental data suggest agricultural soil cooling by up to 4°C at a depth of 10 cm at mid-latitude (43°N), with cooler soil storing more carbon (Hartley et al, 2021).…”
Section: Potential Methods For Direct Climate Coolingmentioning
confidence: 99%
“…There are a variety of shade cloths in use at production nurseries, ranging from standard black to reflective/metallic white, with shade reducing capabilities of 30-80%. Shade cloths often are marketed as a way of preventing summer heat stress, but they also have been shown to improve tree stem strength through a reduction in excessive vertical growth (Fare 2012, Mohawesh et al 2022. By reducing solar radiation of overwintering trees, we hypothesize that providing shade to container-grown ornamental trees also will promote accumulation of chill hours and prevent loss of dormancy, thus reducing risk of frost injury and subsequent biotic injuries. )…”
Section: Introductionmentioning
confidence: 95%
“…This decreases the total temperature of the canopy and reduces water use [ 40 ]. Extensive research has been conducted to prove the effects of net shading on crops [ 41 , 42 , 43 ]. Nicolas et al [ 44 ], for instance, showed that transpiration in shaded apricot ‘Bulida’ trees was lower than in trees exposed to direct solar radiation.…”
Section: Orchard Establishment and Horticultural Managementmentioning
confidence: 99%